Neuroconduccion of the medium nerve in the carpal tunnel in data-entry personnel of two companies of telecommunications. Medellín. October-November 2005 - Luis F. De Subiría; Martha L. Escobar; Fernando Ramírez (Universidad de Antioquia, 2008)
Objetive: This study was carried out in order to know the comportment of the median nerve's impulse speed at the carpal tunnel associated to the exposure time to the fingers' repetitive motion risk factor. Methodology: This study was applied to data-entry personnel at two companies in the city of Medellin, Colombia, during October and November of 2005. Age, gender, labour exposure time, dominant hand and pathological antecedents associated to the carpal tunnel syndrome variables were investigated. Clinical test and a median nerve conduction test were applied to the workers. Discussion: 55 data-entry workers were evaluated, for a total of 110 hands. The survey included ages between 19 and 40 years old and an average age of 28; 86% of the studied subjects were women; 91% of surveyed subjects declared themselves as right-handed and 60% had a normal weight. Subjects had worked between 12 and 180 months as data-entry personnel with an average time of 83 months, working 48 hours a week. No relevant statistical link was found between labour exposure time and median nerve conduction. Results suggest that doing repetitive movements at work as the only risk factor is not a cause of nerve conduction disorder in the median nerve.